Normative data on the n-back task for children and young adolescents - Pelegrina, Santiago; Lechuga, M. Teresa; García-Madruga, Juan A.; Elosúa, M. Rosa; Macizo, Pedro; Carreiras, Manuel; Fuentes, Luis J.; Bajo, M. Teresa (Frontiers in Psychology, 2015)
The n-back task is a frequently used measure of working memory (WM) in cognitive neuroscience research contexts, and it has become widely adopted in other areas over the last decade. This study aimed to obtain normative data for the n-back task from a large sample of children and adolescents. To this end, a computerized verbal n-back task with three levels of WM load (1-back, 2-back and 3-back) was administered to 3722 Spanish school children aged 7–13 years. Results showed an overall age-related increase in performance for the different levels of difficulty. This trend was less pronounced at 1-back than at 2-back when hits were considered. Gender differences were also observed, with girls outperforming boys although taking more time to respond. The theoretical implications of these results are discussed. Normative data stratified by age and gender for the three WM load levels are provided.